Creating a bilingual dictionary of collocations: A learner-oriented approach - Vaupot, Sonia (Universitas Pendidikan Indonesia, 2021)
Considering the lack of specialised dictionaries in certain fields, a creative way of teaching through corpora-based work was proposed in a seminar for master’s students of translation studies (University of Ljubljana, Slovenia). Since phraseology and terminology play an important role both in specialised translation and in the learning path of students of translation studies, this article presents an active approach aimed at creating an online lexicographic resource in languages for specific purposes by using the didactic tool and database ARTES (Aide à la Rédaction de TExtes Scientifiques/Dictionary-assisted writing tool for scientific communication) previously developed at the Université de Paris (France). About thirty Slovene students enrolled in the first year of master’s study have been participating in the bilateral project since 2018. The aims of such an activity are multiple: students learn in a practical way how to compile comparable corpora from the internet, using the online corpus software Sketch Engine, to find similar linguistic constructions in the source and target languages. They also learn to create an online bilingual phraseological and terminological dictionary to facilitate the translation of specialised texts. In this way, they acquire skills and develop some knowledge in translation, terminology, and discourse phraseology. The article first describes the ARTES online database. Then, we present the teaching methodology and the students’ work, which consists of compiling corpora, extracting and translating collocations for the language pair French-Slovene, and entering them in the ARTES database. Finally, we propose an analysis of the most frequent collocation structures in both languages. The language pair considered here is French and Slovene, but the methodology can be applied to any other language pair.